Analisis Studi Kelayakan Bisnis Kopi kalean Pada Aspek Aspek Pemasaran - Selpia Hendawani Sihombing; Lionsy Sitanggang; Dwi Astuti (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the business feasibility of kopi kalean kebon jati cibitung from a marketing perspective. The research employs a descriptive method with a case study approach, gathering data through observation, interviews, and documentation. The analysis focuses on market segmentation, marketing strategies, marketing mix (4Ps), and customer satisfaction levels. The findings reveal that kopi kalean kebon jati has significant market potential with clear segmentation, effective promotional strategies, and competitive pricing. Its strategic location and consistent product quality are key advantages in attracting customers. However, challenges exist in addressing market competition and maintaining customer loyalty. Therefore, the business is deemed feasible for further development with several recommendations for improvement in digital promotion and product innovation.